Pulmonary Innate Immune Response and Melatonin Receptors in the Perinatal Stress - Janaínna Grazielle Pacheco Olegário; Marcos Vinícius Silva; Juliana Reis Machado; Laura Penna Rocha; Marlene Antônia Reis; Camila Souza de Oliveira Guimarães; Rosana Rosa Miranda Corrêa (Clinical and Developmental Immunology)
Objective. To analyze the cytokines of the innate immune pulmonary response and the capacity for local response to melatonin according to the perinatal stress. Methods. 49 cases of pediatric autopsies were evaluated, divided according to cause of death, perinatal stress, gestational age, and birth weight. The percentages of IL-6, C-reactive protein (CRP), IL-1β, TNF-α, and melatonin receptor were evaluated by immunohistochemistry. Results. The IL-6 expression was higher in the children showing chronic stress, anoxia, and infection. The IL-6 expression showed a progressive increase according to the relation between weight and GA. There was no significant difference in the expression of IL-1β and TNF-α. The CRP expression was higher in the cases showing chronic stress and premature cases. The expression of melatonin receptors was significantly higher in the cases showing chronic stress, being more evident in the cases showing infection. Conclusion. The cause of death and the type of stress influence the expression in situ of melatonin and cytokines of the innate immune pulmonary response. The evaluation of IL-6 and CRP may contribute to the understanding of the evolution of neonates with chronic stress. The greater sensitivity of the lung to melatonin in these cases may indicate an attempt at controlling the immunological response, in an attempt to diminish the harmful effects of stress.